Quantum Mechanical Meaning of the Charge Transfer Resistance - Sánchez, Yuliana Pérez [UNESP]; Santos, Adriano [UNESP]; Bueno, Paulo Roberto [UNESP] (American Chemical Society (ACS), 2022)
In a previous work on the quantum rate interpretation of the electron transfer occurring in heterogeneous electrochemical interfaces, we demonstrated that a quantum mechanical rate principle can be used to calculate the electron transfer rate constant of diffusionless electrochemical reactions. This calculation was demonstrated to be possible by simply taking a single specific value of a current-voltage electrochemical curve from which the quantum capacitance of the electrochemical interface is obtained. The method is supported by the fact that the quantum of conductance is related to the quantum capacitance and the ratio between these quantities defines the quantum rate of the electrochemical reaction whenever the quantum degeneracy is rightly defined. In the present work, we applied capacitance-derived electrochemical impedance spectroscopy not only to confirm our conclusions stated in previous works but also to establish the quantum mechanical meaning of the charge transfer resistance which, as will be demonstrated, is correlated to the transmission coefficient within the quantum rate theory. Accordingly, we experimentally demonstrated that the resistance to the transfer of a single charge at the interface occurred with a value of ∼13.0 ± 0.4 kΩ that conformed with the nanoscale electronic interpretation of the quantum of resistance, theoretically expected to be ∼12.9 kΩ. The value of ∼13 kΩ, as a physical and quantized resistive limit, not only agrees with the theory but also cannot be interpreted in isolation, requiring a consideration of resistances of contact and electrolyte contained in the definition of charge transfer resistance. Our findings confirm that electrochemistry and nanoscale electronics, within a suitable quantum mechanical interpretation of the electron dynamics, have a common foundation in quantum mechanics. This work indicates that controlling the properties of electrochemical interfaces at the nanometer molecular scale will enable the development of novel and advanced electrochemical quantum devices.